EVALUASI PROGRAM PENINGKATAN PERANAN WANITA MENUJU KELUARGA SEHAT SEJAHTERA (P2WKSS) DALAM PEMBINAAN KELUARGA SEJAHTERA DI KELURAHAN KURAO PAGANG KOTA PADANG - asdaliani asdaliani; Nora Eka Putri (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2019)
This study discusses the Evaluation of the Program for Increasing the Role of Women Towards Healthy andProsperous Families (P2WKSS) in the Development of Prosperous Families in Kurao Pagang Sub-District,Nanggalo District, Padang City which aims to create a healthy and prosperous family. The method used inthis study is descriptive qualitative. This research was conducted at the Office of Women's Empowerment,Child Protection, Population and Family Planning Control, and especially in RW 08, Kurao PagangVillage. Furthermore, the selection of research informants was done by incidental sampling and purposivesampling. Based on incidental sampling techniques, some of the assisted residents in 75 families thatresearchers met by chance were in the research field, while in purposive sampling, the government had theauthority and responsibility for implementing the P2WKSS Program. Data collected by means of interviews,observation, and documentation studies. The research findings that researchers can in the field about theP2WKSS Program start from the implementation, the factors that influence the success of the programimplementation, and the government's efforts to overcome the factors that influence the failure. Based onthe research, it was found that (1) the P2WKSS program in the Kurao Pagang Sub-district has broughtimprovements to the region but has not brought increased income for the target people, (2) there areproblems with resource factors, (3) preventive efforts and promotive efforts by the government in theimplementation of the P2WKSS Program.